2014
DOI: 10.1177/1358863x14556852
|View full text |Cite
|
Sign up to set email alerts
|

Regular physical activity is associated with improved small artery distensibility in young to middle-age stage 1 hypertensives

Abstract: The aim of the present study was to investigate the association of physical activity with small artery elasticity in the early stage of hypertension. We examined 366 young-to-middle-age stage 1 hypertensives (mean blood pressure 145.6±10.3/92.5±5.8 mmHg), divided into two categories of physical activity, sedentary (n=264) and non-sedentary (n=102) subjects. The augmentation index was measured using the Specaway DAT System. Small artery compliance (C2) was measured by applanation tonometry, at the radial artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
2
13
0
1
Order By: Relevance
“…In this study, we showed a strong and independent association between leisure-time physical activities and small artery elasticity index independent of possible confounders both at baseline and approximately 10 years later. The association between SAEI and LTPA was strong and [14]. In line with our findings, they also found that physical activity predicted better SAEI.…”
Section: Main Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we showed a strong and independent association between leisure-time physical activities and small artery elasticity index independent of possible confounders both at baseline and approximately 10 years later. The association between SAEI and LTPA was strong and [14]. In line with our findings, they also found that physical activity predicted better SAEI.…”
Section: Main Findingssupporting
confidence: 91%
“…Small artery elasticity index (SAEI) seems to be strongly associated with changes in the artery wall associated with hypertension [14], diabetes mellitus, and atherosclerosis compared to LAEI [6]. Similarly, it is strongly associated with chronic heart disease, stroke and heart failure [4].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial stiffness is defined as reduced elasticity of the artery which renders the vessel unresponsive to changes in intravascular pressure (11). This elasticity is crucial in ensuring a smooth stream of blood from cyclical ventricular ejection during its delivery to the end organs (12). As the artery becomes less distensible, the JEPEM [234.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, podemos dizer que a redução da bradicardia estaria associada ao envelhecimento enquanto a redução da taquicárdica esta associada a privação dos hormônios e envelhecimento presente tanto nos grupos 129 ooforectomizados quanto envelhecidos. Comprometimentos na sensibilidade barorreflexa relacionadas à idade tem sido associados com alterações na complacência arterial, alterações da integração autonômica central, redução do fluxo vagal e diminuição da densidade do receptor muscarínico do nodo sinusal (BRODDE et al, 1998;ITOH;BUNAG, 1992 A idade vem sendo associada com aumento de PA, bem como uma diminuição na complacência arterial e de distensibilidade do sistema arterial, especialmente no mundo ocidental (SALADINI et al, 2014). Dentre esses achados, a complacência arterial tem sido vista como um poderoso determinante de risco cardiovascular (BLACHER et al, 1999).…”
Section: Avaliação Do Perfil Hemodinâmico E Do Controle Autonômico Caunclassified